Evaluating The Effectiveness Of Laparoscopic Longitudinal Gastric Resection Surgery On Early Postoperative Complications And Obesity-Related Comorbidities (Texas Journal of Medical Science, 2024)
Studying of the corrective effect of longitudinal gastrectomy on concomitant diseases in patients with morbid obesity. This scientific work is based on the results of a comprehensive examination and treatment of 187 patients with MO who were treated in the our clinical bases from 2021 to 2023. The analysis of comorbidities in the compared groups showed that one or more comorbidities were detected in 72% of the control group, 77% of the main group. The main part of these patients was made up of patients with obesity of the III degree. The proposed modification of SG in morbidly obese patients improved the cardioesophageal function and the strength of the gastroduodenal staple line, eliminating the observed complication of staple line failure of 2.2%. It also led to a decrease in the symptoms of gastroesophageal reflux disease from 14% to 6.1%. In the longitudinal gastric resection procedure, the use of local hemostatic powder "HEMOBEN" along the gastric staple line reduced the bleeding complication from 3.2% to 1.1% and the duration of the procedure by an average of 15±3 minutes.In particular, if in the control and main groups, arterial hypertension was detected in 50 and 59.3% of patients before the surgical procedure, then 3 months after the surgical procedure, an increase in blood pressure was observed in 45.4 and 37% of the patients. After surgery, the clinical signs of arterial hypertension and arthralgia in patients with morbid obesity gradually disappeared with the elimination of obesity. In conclusion, these clinical signs were caused by obesity, and its elimination led to the disappearance of these clinical signs.